Political Thought in Bosnia and Herzegovina Between the Two World Wars: Primary Determinants, Contextual Experiences, and Thematic Orientations - Elvis Fejzić (Društvene i Humanističke Studije, 2023)
Political thought between the two world wars in Bosnia and Herzegovina was marked by substantive educational activity and production with pan-political characteristics. For this reason, it is important to investigate to what extent the thematic focus of Bosnian political thought at that time corresponds to the most significant contextual events in the domestic and extra-national spheres of politics. The theoretical approach that indicates that political activity, behavior, and thinking are determined by challenging contextual determinants represents one of the classic and fundamental research models in political science. Nevertheless, the achieved level of political awareness, the development of political culture, and the established system of government in a specified state context can significantly influence the thematic range of political opinion as well as the participation of citizens in the political process. Therefore, it is necessary to take into account the mentioned contextual and variable determinants in the analysis of the thematic orientation of Bosnian political thought in the period between the two world wars. The dominant narratives and thematic preoccupations in Bosnian political thought at the time will be identified and detected, after the research is conducted, and their compatibility with the key political challenges will be examined.